2007
DOI: 10.2341/07-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Curing Units and Staining Solutions on the Color Stability of Resin Composites

Abstract: This study investigated the effects of two different light curing units and two staining solutions on the color stability of a hybrid composite and a nanohybrid composite after different immersion periods. Thirty disk-shaped specimens (10 mm in diameter, 2-mm thick) were fabricated for each of the resin composites, Clearfil AP-X and Filtek Supreme. The specimens were randomly divided into two groups according to the curing unit used: Group I specimens (n = 15) were cured with a quartz-tungsten-halogen (QTH) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
20

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 26 publications
(28 reference statements)
7
75
0
20
Order By: Relevance
“…Villalta et al 24) showed that a nanocomposite (Filtek Supreme) underwent a more significant color change than a microhybrid composite (Esthet-X) as a result of staining with coffee or red wine solutions. Yazici et al also reported that the nanocomposites had a higher color change than the microhybrid composites after staining 15) . These results are in agreement with our study, which found that the microhybrid composite resin (AT), which had a greater inorganic volume (77.4%), showed the lowest ΔE values for all tested solutions when compared to the nano composite resin (GN), but this difference was not statistically significant (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Villalta et al 24) showed that a nanocomposite (Filtek Supreme) underwent a more significant color change than a microhybrid composite (Esthet-X) as a result of staining with coffee or red wine solutions. Yazici et al also reported that the nanocomposites had a higher color change than the microhybrid composites after staining 15) . These results are in agreement with our study, which found that the microhybrid composite resin (AT), which had a greater inorganic volume (77.4%), showed the lowest ΔE values for all tested solutions when compared to the nano composite resin (GN), but this difference was not statistically significant (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Um and Ruyter revealed that discoloration by coffee was due to both adsorption and absorption of colorants. This absorption and penetration of colorants into the organic phase of the materials were probably due to compatibility of the organic phase with the yellow colorants of the coffee 15) . In the present study, color change values for all resin composite restorative materials in cola were less than 3.3 after 60 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many studies have extensively reported the harmful effects of coffee, tea, grape juice, yerba mate and cola drinks on dental composites. [8][9][10] More recently, other reseachers 4,[11][12][13] reported the color changes promoted by lemon juice, cherry juice, carrot juice, red wine, snow cone syrup and grape drink. However, there are some other important colored foods that are very common in the patient's diet, such as ketchup and mustard, and yet, the effects of these foods on the color of composites have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a veneering resin composite is being used as an esthetic prosthetic material to reproduce the natural tooth crown color. However, due to physico-chemical deterioration, discoloration may occur and replacement may be necessary [1][2][3] . Ceramics have proven to be superior in chemical and color stability and to be adequately biocompatible 4,5) .…”
Section: Introductionmentioning
confidence: 99%